Pof8 is a La-related protein and a constitutive component of telomerase in fission yeast - Diego J. Páez-Moscoso (Nature Portfolio, 2018)
The core of the telomerase holoenzyme is composed of the reverse transcriptase and the non-coding RNA template. Here the authors identify Pof8 as a new constitutive component of fission yeast telomerase, loss of which causes telomerase assembly defects and critically short telomeres.